Design, Fabrication and Control of a Soft Robotic Arm - Batu, Batu (Auckland University of Technology, 2025)
Soft robots are a class of robots made from flexible materials, allowing them to operate effectively in complex and unstructured environments, which is different from traditional rigid robots. This thesis focuses on a soft robotic arm with a folded origami structure, exploring its control system and manufacturing method. In manufacturing, experiments were conducted to test the adhesion strength of different materials. Based on the results, the overall fabrication method was defined, and a new fabrication method for the origami soft robot arm was proposed. This method ensures the structural integrity of the soft robotic arm and improves production efficiency. Regarding the control system, most current soft robot control systems rely on internal sensors or external vision for mechanism spatial positioning. This thesis presents a control system integrating internal sensors and external stereo vision. It can accurately regulate the robot's response, preventing damage to the pneumatic drive system and soft robot structure from excessive compression and extension. The control system enables accurate spatial positioning and configuration identification of the soft robot using cameras, even in the absence of a mechanical or analytical model. Furthermore, the system incorporates feedback signals from the soft robot's internal air pressure sensor, enabling the real-time calculation of its spatial position and shape while simultaneously measuring the fluctuations in internal pressure. A closed-loop control system is established by integrating visual feedback and air pressure feedback, safeguarding the soft robot's components and the origami's three-dimensional structure while the user operates the robot. Additionally, this thesis introduces a stereo vision pipeline suitable for MATLAB based on the control system's stereo vision. This pipeline simplifies the establishment of a stereo vision system and enables rapid target object identification, enhancing the soft robotic arm's operational efficiency and accuracy. The new control system, soft robot design, and fabrication method provide a reference for the control and manufacturing of origami soft robots.